The wilderness [videorecording (DVD)] - King, Spencer; Doohan, Hunter, 1994-; Johnson, Lamar, 1994-; Holliday, Aaron; Jaeger, Sam (Dark Star Pictures, 2026)
Kidnapped and abandoned in the Utah desert, a group of troubled boys are forced into a ruthless "Wilderness Therapy" program. Cut off from the world, they must survive both the elements and the mind games of a cruel director.